2019
DOI: 10.1016/j.jdsr.2018.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of current adhesive systems when bonding to CAD/CAM indirect resin materials: A review of 32 publications

Abstract: SummaryThe purpose of this review was to assess the available literature regarding bonding between current adhesive systems and computer-aided design/computer-aided manufacturing (CAD/CAM) indirect resin materials, to provide clinicians with a comparative overview of the relevant bonding procedures. An electronic search was performed through PubMed based on the keywords CAD/CAM and dental bonding. Additional relevant literature was obtained from the citations in the articles. A total of 313 papers were identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 39 publications
2
42
1
1
Order By: Relevance
“…Yanikoglu et al 10 examined the shear bond strengths of light-polymerized composites and cold-polymerized acrylics to acrylic teeth and reported that, if an adequate bonding agent is used, enhanced bonding can be attained with a composite material. In a systematic review, Mine et al 32 concluded that materials containing methyl methacrylate improved the bonding of CAD/CAM PMMA resin materials. Previous research 10,17,32,33 and the present study results (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Yanikoglu et al 10 examined the shear bond strengths of light-polymerized composites and cold-polymerized acrylics to acrylic teeth and reported that, if an adequate bonding agent is used, enhanced bonding can be attained with a composite material. In a systematic review, Mine et al 32 concluded that materials containing methyl methacrylate improved the bonding of CAD/CAM PMMA resin materials. Previous research 10,17,32,33 and the present study results (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The physical adsorption is affected by surface topography (roughness) of the substrate 12,14) which will change the surface area and the wettability 15) , subsequently improve its surface energy 12) . Surface pretreatment with sandblasting (SB) is recommended by the manufacturer for all DF-RCBs 11,13,[16][17][18][19][20][21][22] to increase their roughness. SB with 50 µm alumina particles under a controlled air pressure of 0.1-0.2 MPa has been reported as the most effective method for bond durability 16) , but it may affect the fatigue strength and long-term durability of DF-RCBs 23,24) due to the development subsurface cracks (1-10 µm) 23) .…”
Section: Introductionmentioning
confidence: 99%
“…To obtain a strong resin bond, the dispersed nanoparticlefilled composite resin (i.e. Lava Ultimate) should be pretreated through airborne-particle abrasion with alumina particles, followed by application of silane [2,[16][17][18]. On the other hand, the resin infused ceramic hybrid (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the resin infused ceramic hybrid (i.e. VITA Enamic) should be applied with hydrofluoric acid etching and then silanized [2,[16][17][18]. This difference in the adhesive procedure is due to the composition of the resin-based CAD/CAM materials (Table 1).…”
Section: Discussionmentioning
confidence: 99%